Hubungan Penggunaan Media Sosial Whatsapp Berkonten Pornografi dengan Perilaku Seksual Berisiko pada Remaja di SMKN X Jakarta Timur - Nurwati Rettob; Murtiningsih Murtiningsih (Jurnal Akademika Baiturrahim Jambi, 2021)
WhatsApp is social media which very popular in the society. Using social media such as WhatsApp has a  positives and negatives impacts. The negative impact of WhatsApp is the teenager which access and share the link of pornographies. The aim of this research is to know the relation between the users of WhatsApp as social media which has content of pornographies and sexual behaviors toward teenagers at SMKN X East Jakarta. The methodology  in this research is using correlation study. The instrument which is using questionnaire of user WhatsApp as social media and questionnaire which for the people who has big risk to sexual behaviors. Population which uses in this research is students at SMKN X East Jakarta which took 104 respondents as sample. The result from univariate analyses in this research is showing us that most of the respondents which using WhatsApp as social media has 58 respondents (55,8%) that got negative impacts. And for sexual behaviors 58 respondent (55,8%) which categorize to have big risk. The result of analyses of chi square, that shows us that there is signification relation between the users of WhatsApp as social media which has content of pornographies and sexual behaviors towardteenagers at SMKN X East Jakarta with value p-value (0,040), and value OR=2,470 which means that if the users of social media such WhatsApp that has contents of pornographies (negative) then teenagers have big opportunity to do sexual behaviors